Derajat Kristalinitas dan Struktur Anatomi Kayu Jati Muna Akibat Perlakuan Panas - Fendi Fendi; Dian Kurniaty; Saptadi Darmawan (Jurnal Ilmu Pertanian Indonesia, 2017)
Teak wood (Tectona grandis L.f.) is an important part of building material in Muna, Southeast Sulawesi. This study aims to investigate the characteristics of teakwood Muna namely the degree of crystallinity and the anatomical structure of teakwood after heat treatment for 0.5-12 hours. The results of XRD analysis showed crystallinity diameter without treatment and after treatment of temperature at 90, 120, 150, dan 180 C decreased with increasing temperature namely 5.95; 5.97; 6.02; 6.2; and 7.04 nm. SEM analysis showed teakwood surface profile changes after heat treatment applied.